Association between autonomy support, academic motivation, and life skills in pre-service physical education teachers and pre-service sport coaches - Ortiz-Rodríguez, Verónica; Vergara-Torres, Argenis P.; Ramírez-Nava, Ruben; Tristán, José; López-Walle, Jeanette M. (Frontiers in Education, 2024)
This study aimed to analyze the relationships between the perception of the autonomy-support style created by the professor, the global academic intrinsic motivation and its three subtypes (to know, toward accomplishments, and to experience stimulation), and the life skills of future physical education (PE) teachers and sports coaches. The participants were 583 students (Mage = 20.77 years, SD = 2.94; 65% were men) belonging to a higher education program specialized in the training of PE teachers and sports coaches in Mexico. The results of the structural equation models showed that the perception of the autonomy-support style adopted by the professors was positively and significantly related to global academic intrinsic motivation and its three subtypes, and these were positively and significantly associated with each life skill. The mediation analyses confirmed the mediating role of global academic intrinsic motivation and subtypes between the perception of the autonomy-support style adopted by the professors and the student’s life skills. In conclusion, to promote the development of life skills in future PE teachers and sport coaches, it will not only be enough for their teachers to generate positive environments of autonomy-supportive styles, but they must also have intrinsic reasons to enhance these skills.